Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

From plants to feces: pilot applications of FTIR spectroscopy for studies on the foraging ecology of an avian herbivore - U. Nopp-Mayr; M. Zohmann-Neuberger; J. Tintner; M. Kriechbaum; R. Rosenberger; H. Nopp; A. Bosa; E. Smidt (Journal of Ornithology, 2020)
Studies on the foraging ecology of wildlife species are of fundamental importance, as foraging decisions are closely linked to ecological key issues such as resource partitioning or population dynamics. Using Black grouse as a model system, we applied Fourier-transform infrared spectroscopy (FTIRS) to address some key questions in foraging ecology: (1) does FTIRS allow for determining plant taxa and plant parts? Can FTIRS suggest variation in digestibility of food and physiological mechanisms of consumers? (2) Can FTIRS be used to track changes in diets among populations? (3) Can FTIRS capture plants' phenology and shifts in diet? To answer these questions, we analyzed crop and gizzard contents of Black grouse via FTIRS looking for specific spectra and bands of plant taxa and plant parts. We compared spectral signals of undigested plant material and intestinal droppings, gained from wild-living birds and from aviaries. Our analyses yielded characteristic spectral fingerprints for several food plants and plant parts. Spectral fingerprints could differentiate between needles of J. communis and P. mugo and between fruits of J. communis, Sorbus sp., and Vaccinium sp. Spectral signals differed more between undigested material and crop samples than between crop and gizzard samples. Differences were more pronounced for berries than for needles. Apart from these differences, some fingerprints persisted for certain food items. The diverse foraging regime of wild-living individuals compared to captive Black grouse was reflected by spectral signals. Thus, FTIRS is a promising approach to explore variation in food choice of grouse species by means of non-invasively gained fecal samples.

Duration of viral shedding and factors associated with prolonged shedding among inpatients with influenza treated with oseltamivir: a prospective cohort study - J. Khoury; M. Szwarcwort; Z. Kra-oz; M. Saffuri; K. Seh; T. Yahalomi; E. Braun; Z. S. Azzam; M. Paul; A. Neuberger (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Risk factors for and impact of carbapenem-resistant Acinetobacter baumannii colonization and infection: matched case–control study - O. Henig; G. Weber; M. B. Hoshen; M. Paul; L. German; A. Neuberger; I. Gluzman; A. Berlin; C. Shapira; R. D. Balicer (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The significance of persistent fever in the treatment of suspected bacterial infections among inpatients: a prospective cohort study - A. Neuberger; D. Yahav; V. Daitch; Y. Akayzen; L. Farbman; T. Avni; L. Leibovici; M. Paul (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Localization of osteoblast inflammatory cytokines MCP-1 and VEGF to the matrix of the trabecula of the femur, a target area for metastatic breast cancer cell colonization - Karen M. Bussard; Noriaki Okita; Neil Sharkey; Thomas Neuberger; Andrew Webb; Andrea M. Mastro (Clinical & Experimental Metastasis, 2010)

Effects of Sublethal Zn++ and Cd++ Concentrations on Filtration Rate, Absorption Efficiency and Scope for Growth in Donax trunculus (Bivalvia; Donacidae) - Lya Neuberger-Cywiak; Y. Achituv; E. M. Garcia (Bulletin of Environmental Contamination and Toxicology, 2007)

Smoking cessation at the workplace: 1 year success of short seminars - HP Hutter; H Moshammer; M Neuberger (International Archives of Occupational and Environmental Health, 2006)

Sublethal Effects of Zn++ and Cd++ on Respiration Rate, Ammonia Excretion, and O:N Ratio of Donax trunculus (Bivalvia; Donacidae) - L. Neuberger-Cywiak; Y. Achituv; E. M. Garcia (Bulletin of Environmental Contamination and Toxicology, 2005)

Effects of Zinc and Cadmium on the Burrowing Behavior, LC 50 , and LT 50 on Donax trunculus Linnaeus (Bivalvia-Donacidae) - L. Neuberger-Cywiak; Y. Achituv; E. M. Garcia (Bulletin of Environmental Contamination and Toxicology, 2003)

Rasche Carboxihmoglobinbestimmung mittels nichtdispersiver Ultrarot-Gasanalyse - H. Hauck; M. Neuberger; W. Resch (Archives of Toxicology, 1976)